Багатокритеріальна оцінка технологічної придатності ферментованих рослинних субстратів для використання в м’ясних системах - Баль-Прилипко, Лариса Вацлавівна; Ніколаєнко, Микола Станіславович; Сердюк, Марина Єгорівна; Бандура, Валентина Миколаївна; Іванова, Ірина Євгенівна; Bal-Prylypko, Larysa; Nikolaenko, Mykola; Serdyuk, Maryna; Bandura, Valentyna; Ivanova, Iryna (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Об’єктом дослідження були ферментовані рослинні субстрати (спельта, льон, ламінарія, глива), отримані після 18 діб ферментації. Мета досліджень полягала в проведенні інтегральної оцінки придатності досліджуваних субстратів для різних груп м’ясних продуктів на основі багатокритеріального підходу. Показано, що ферментація зумовлює багатофакторні зміни кислотного стану, вуглеводного та білково-азотного профілю, а також параметрів вологоутримання, які формують індивідуальний функціонально-технологічний профіль кожного субстрату. Для узагальнення різновимірних критеріїв використано метод зваженої суми. За результатами оцінки льон отримав максимальні інтегральні бали в більшості груп виробів, тоді як спельта продемонструвала найвищу придатність для сирокопчених і сиров’ялених виробів. Ламінарія та глива характеризувалися проміжними значеннями й можуть розглядатися як функціональні модифікатори структури та смакоароматичного профілю. /// EN: The object of the study was fermented plant substrates of spelt, flax, kelp and oyster mushrooms after eighteen days of fermentation and their potential use as ingredients in various meat product technologies. The aim of the work was to conduct an integral multi-criteria assessment of the suitability of these substrates for different groups of meat products, taking into account their functional and technological characteristics. During the fermentation process, multifactorial changes in acidity, carbohydrate and protein-nitrogen profile, as well as indicators related to water-holding capacity were established, which led to the formation of an individual functional and technological profile of each substrate. Individual analytical indicators do not allow objectively assessing their practical suitability in meat systems, since the effectiveness of the ingredient is determined by the cumulative effect on the structure, stability and rheological behavior of the protein-fat system. For this purpose, the weighted sum method was used as a tool for multi-criteria analysis. All fermentation indicators were classified according to the direction of optimization: the hydrogen indicator was considered as a target criterion taking into account the optimal interval of values for different product groups; parameters, the reduction of which is technologically feasible, were attributed to cost criteria; indicators, the increase of which contributes to the formation of the desired structural-mechanical, sensory and functional properties, were defined as useful criteria. Scenario-based weighting factors were established for each group of meat products, taking into account the specifics of emulsion, pate, semi-smoked, cooked-smoked, rawdried, raw-smoked, ground and whole-muscle products. The results of the analysis showed that flax is characterized by the highest integral scores in most product groups, while spelt is most suitable for raw-dried and raw-smoked products. Laminaria and oyster mushrooms demonstrate intermediate integral values and can be considered as functional modifiers depending on the technological scenario. The obtained data create a scientifically sound basis for further experimental testing as part of complex meat systems and the development of practical recommendations for optimizing recipes and technological regimes.
Multi-criterion assessment of the technological suitability of fermented plant substrates for use in meat systems
Keywords: ферментація; рослинні субстрати; багатокритеріальна оцінка; вологоутримувальна здат- ність; активність води; м’ясні вироби; fermentation; plant substrates; multi-criteria evaluation; moisture retention capacity; water activity; meat products